THE EFFECT OF ENTREPRENEURIAL ORIENTATION, IT AND SERVICE INNOVATION ON THE PERFORMANCE CULINARY MSMES AT THE PANDEMIC 2020-2021 - Edi Wibowo; Feronika Martha Azizah (Transpublika Publisher, 2022)
This study aims to analyze the effect of entrepreneurship orientation, information technology, and service innovation on the performance of culinary MSMEs in Banjarsari, Surakarta during the 2020-2021 pandemic. This research was both qualitative and quantitative. The sample in this study were 121 culinary MSMEs with purposive sampling method. Data were analyzed using multiple regression analysis techniques. The results showed there was entrepreneurial orientation, information technology and service innovation had a significant effect on the performance of culinary MSMEs in Banjarsari, Surakarta during the 2020-2021 pandemic. As for suggestion for MSME owners that MSMEs are expected to have entrepreneurial orientation ideas because entrepreneurship skills are needed in realizing marketing strategies in order to obtain a good competitive advantage through the value of responsiveness to customer needs.